2018
DOI: 10.1016/j.curtheres.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Single Intra-Articular Injection in Knee Osteoarthritis: A Multicenter Open Prospective Study (ART-ONE 75) with Placebo Post Hoc Comparison

Abstract: BackgroundViscosupplementation of the synovial liquid, by intra-articular injection of hyaluronic acid, is a widely used symptomatic treatment in knee osteoarthritis. Besides products designed for multi-injections (typically 3–5 injections at 1-week intervals), special interest is being given to single-injection products that offer specific advantages such as the reduction of the number of visits to the doctor and the number of invasive interventions with their associated risks. However, a question remains abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
11
0
6
Order By: Relevance
“…Cross‐linked high molecular weight HA preparations such as Hylan G‐F 20 and Durolane NASHAs and similar HA products with their higher molecular weights, improved visco‐elastic properties, improved residence times and high injection concentrations which facilitate single injection protocols have clearly provided an improvement in the clinical treatment provided by visco‐supplementation. A recent comparison of the efficacy of corticosteroids, visco‐supplementation, PRPs, and MSCs for improved joint function has shown that each have positive attributes .…”
Section: Future Researchmentioning
confidence: 99%
“…Cross‐linked high molecular weight HA preparations such as Hylan G‐F 20 and Durolane NASHAs and similar HA products with their higher molecular weights, improved visco‐elastic properties, improved residence times and high injection concentrations which facilitate single injection protocols have clearly provided an improvement in the clinical treatment provided by visco‐supplementation. A recent comparison of the efficacy of corticosteroids, visco‐supplementation, PRPs, and MSCs for improved joint function has shown that each have positive attributes .…”
Section: Future Researchmentioning
confidence: 99%
“…Of these, 57 included data for IA HA mono-injection 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70. At the end, 28 studies were included,43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70 whereas 29 studies were removed for 1 or several of the following reasons:Two studies were in combination with surgery: anterior cruc...…”
Section: Resultsmentioning
confidence: 99%
“…Selon nos observations, la présence ou l'absence de patients au stade KL IV, a une nette influence sur les résultats cliniques. Prenant en compte le profil KL, l’étude autorise des comparaisons avec les autres essais réalisés avec ARTHRUM H 2% 4 , 5 , 6 , 7 et avec ARTHRUM visc 75 [15] , une version alternative d'ARTHRUM, conçue en injection unique. Pour résumer ces résultats, décrits dans le Tableau 4 , les groupes ARTHRUM incluant 12% de stade KL IV ou davantage, ont procuré des améliorations plus modérées – mais toujours significatives – pour les sous-scores WOMAC (douleur et fonction) et pour les pourcentages de répondeurs OMERACT-OARSI, à M6.…”
Section: Discussionunclassified